Insentif Pajak PMK 86/2020, Norma Subjektif, Modernisasi Sistem Perpajakan Dan Kepatuhan Wajib Pajak UMKM - Gabrielle Merry Yobelia Yobelia; Septian Bayu Kristanto (Jurnal Akuntansi, 2022)
The purpose of this study is to examie the effect of PMK 86/ 2020 tax incentives, subjective norms, and modernization of the tax system on MSME taxpayer compliance during the COVID-19 pandemic in Tangerang City. From 105 samples in the age category and NPWP ownership category, it have been found that: 1) the PMK 86/ 2020 tax incentives has a positive effect on the compliance level of MSME taxpayers in Tangerang City during the COVID-19 pandemic, 2) subjective norms has a negative effect on the level of compliance of MSME taxpayers in Tangerang City during the COVID-19 pandemic, and 3) the modernization of the taxation system has a positive effect on the level of taxpayer compliance in Tangerang City during the COVID-19 pandemic. Keywords: Tax incentives, subjective norms, modernization of the tax system, and taxpayer compliance